Systemic Effector and Regulatory Immune Responses to Chlamydial Antigens in Trachomatous Trichiasis - Gall, Alevtina; Horowitz, Amir; Joof, Hassan; Natividad, Angels; Tetteh, Kevin; Riley, Eleanor; Bailey, Robin L.; Mabey, David C.; Holland, Martin J. (Frontiers in Microbiology, 2011)
Trachomatous trichiasis (TT) caused by repeated or chronic ocular infection with Chlamydia trachomatis is the result of a pro-fibrotic ocular immune response. At the conjunctiva the increased expression of both inflammatory (IL1Β, TNF) and regulatory cytokines (IL10) have been associated with adverse clinical outcomes. We measured in vitro immune responses of peripheral blood to a number of chlamydial antigens. Peripheral blood effector cells (CD4, CD69, IFNγ, IL10) and regulatory cells (CD4, CD25, FOXP3, CTLA4/GITR) were readily stimulated by C. trachomatis antigens but neither the magnitude (frequency or stimulation index) or the breadth and amount of cytokines produced in vitro (IL-5, IL-10, IL-12 (p70), IL-13, IFNγ and TNFα) were significantly different between TT cases and their non-diseased controls. Interestingly we observed that CD4+ T cells account for less than 50% of the IFNγ positive cells induced following stimulation. Further investigation in individuals selected from communities where exposure to ocular infection with C. trachomatis is endemic indicated that CD3-CD56+ (classical natural killer (NK) cells) were a major early source of IFNγ production in response to C. trachomatis elementary body stimulation and that the magnitude of this response increased with age. Future efforts to unravel the contribution of the adaptive immune response to conjunctival fibrosis should focus on the early events following infection and the interaction with innate immune mediated mechanisms of inflammation in the conjunctiva.